2015
DOI: 10.1038/ijosup.2015.21
|View full text |Cite
|
Sign up to set email alerts
|

Associations between sleep patterns and lifestyle behaviors in children: an international comparison

Abstract: Sleep characteristics are important correlates of lifestyle behaviors in children. Differences between countries suggest that interventions aimed at improving sleep and lifestyle behaviors should be culturally adapted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(111 citation statements)
references
References 35 publications
5
101
0
Order By: Relevance
“…One national survey, 4 several state (ie, province) and city-level surveys, [11][12][13][14][15][16][17][18] as well as baseline data from an ongoing longitudinal state-level survey 19 were used as data sources for the 2016 Indian Report Card. In addition, we also reviewed appropriate gray literature to complete the grading process.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One national survey, 4 several state (ie, province) and city-level surveys, [11][12][13][14][15][16][17][18] as well as baseline data from an ongoing longitudinal state-level survey 19 were used as data sources for the 2016 Indian Report Card. In addition, we also reviewed appropriate gray literature to complete the grading process.…”
Section: Methodsmentioning
confidence: 99%
“…12 Several accelerometry studies have also been conducted including the International Study of Childhood Obesity, Lifestyle and the Environment (ISCOLE). [13][14][15] All ISCOLE studies in India were conducted in Bangaluru with the same cohort of 9 to 11 year old children with varying sample sizes (ie, Denstal et al [n = 546]; Sarmiento et al [n = 599]; Chaput et al [n = 433]). [13][14][15] These studies demonstrate that children accumulate between 40 and 50 minutes of MVPA per day on average.…”
Section: Overall Physical Activity: C-mentioning
confidence: 99%
See 1 more Smart Citation
“…With the implementation of a 24-h waist-worn accelerometry protocol, ISCOLE researchers had to tackle the challenge of systematically developing, testing and refining definitions and algorithms, first with the US based sample, and subsequently as applied to all the international accelerometer data collected in ISCOLE. 18 The ultimate list of 24-h waist-worn accelerometer-derived nocturnal sleep-related variables, their definitions, and initial benchmark values based on ISCOLE descriptive data are cataloged in a separate manuscript in this supplement. 19 PROVISION OF A DETAILED MODEL OF PARADATA REPORTING Paradata represent the process-oriented data associated with survey administration and are used to standardize communication, facilitate representativeness and comparability, navigate study management, and anticipate and control costs.…”
Section: Development Of Interpretive Infrastructure For Identifying Amentioning
confidence: 99%
“…Finally, a cross-cultural study of children (9-11 years old) in 12 countries found correlations between later bed times and "unhealthy diet patterns," which were defined as increased consumption of fast food, fried foods, soda, etc. (Chaput et al, 2015).…”
Section: Introductionmentioning
confidence: 99%